Tending to stories in feminist theologies: interdisciplinary renderings of faith, hope and love - Kadmos, Helena; Massam, Katharine (Gender, theology and spirituality, 2026)
"Tending to Stories in Feminist Theologies is interested in the place of story-tellers in communities of hope. Where some theologies wrestle for clarity of definition, feminist and other theologies of liberation begin from experience and tend towards story as a vehicle for speaking of the Divine. Ambiguity and precision both find their place. This collection embraces different materials to explore the place of stories and narrative within feminist theology, to explore how meaning 'happens', to seek justice and forge compassion. As for theology, so too with form. This volume does not just discuss but actively demonstrates a variety of ways in which stories can be heard and held. Between and within chapters, the authors weave together artwork, literature, creative nonfiction and poetic form with critically-informed and academic exposition to invite reflection on the place of story in creating solidarity and enabling community. The book contributes to scholarly conversations on feminist theological method, on the relationship between the arts and theology, and on the dialogue between secular and sacred in Australasia and elsewhere"-- Provided by publisher